Mrs. Naunakhte & family : the women of Ramesside Deir al-Medina - Donker van Heel, Koenraad (The American University in Cairo Press, 2017)
The so-called Will of Naunakhte (1154 BCE) has become rightly famous in Egyptology. So where did she come from and what really happened to her 8 surviving children, 4 of whom were daughters? By carefully studying the documents mentioning members of the family and including all the material mentioning the women of the New Kingdom village of Deir al-Medina and other sources, the author once again puts to the forefront the remarkable role played by ordinary women in ancient Egypt